0747 Study Design of an Open-Label Extension and Switch Study for Once Nightly Sodium Oxybate, FT218, in NT1 and NT2 Patients. (27th May 2020) - Wells, C; Dubow, J; Fenton, M; Patel, D; Tyler, C; Seiden, D
Abstract: Introduction: Avadel Pharmaceuticals has developed FT218, a once nightly sodium oxybate (SO) formulation for the treatment of excessive daytime sleepiness (EDS) and cataplexy in narcoleptic patients. REST-ON, a pivotal efficacy/safety study is expected to be completed in the first half of 2020. Previous Phase 1 studies have demonstrated FT218 delivers a pharmacokinetic profile needed for once-nightly dosing. The purpose of this study is to evaluate long-term safety of FT218 in REST-ON completers and dosing strategy when switching from twice-nightly SO to FT218. Methods: The study will enroll NT1/NT2 patients who completed REST-ON or patients switching from stable dose of twice-nightly SO to FT218. REST-ON completers will initiate FT218 at 4.5 g and increase by 1.5 g to the highest tolerated dose or the dose deemed effective (up to 9 g). Switch patients will initiate FT218 at the equivalent/closest dose to their current twice-nightly SO and titrate in accord with safety/efficacy. The study will enroll approximately 250 patients for a duration of two years. Results: The primary endpoint for REST-ON completers will be safety and tolerability. Secondary endpoints for REST-ON completers will include changes in ESS, reported cataplexy and other REM associated phenomena as well as changes in clinician and patient global impression. For switch patients, endpoints will include percentage of subjects that stay on the same, higher or lower dose of FT218 compared to twice-nightly SO, as well as the percentage of subjects who report a preference for the once-nightly dosing regimen. Conclusion: The results of this open label extension/switch study will further elucidate the potential benefits of once-nightly FT218 regarding long term safety/tolerability, nocturnal safety/tolerability and efficacy, and importantly provide dosing and preference data for patients switching from twice-nightly SO to once-nightly FT218. Support: This work was supported by Avadel Pharmaceuticals.